2012
DOI: 10.1002/chin.201247076
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: [Pd(μ‐Br)(PtBu3)]2 as a Highly Active Isomerization Catalyst: Synthesis of Enol Esters from Allylic Esters.

Abstract: Compared to Pd(II) or Pd(0) catalysts, the Pd(I) dimer permits the double bond migration of a wide range of unsaturated substrates which can be further hydrogenated in the presence of a chiral system to optically active saturated esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…150 In 2012, Gooßen's group identified it as a highly active isomerization catalyst for the synthesis of enol esters from allylic esters. 151 [(P(t-Bu) 3 Pd(μ-Br))] 2 has been employed as a precatalyst, 145,152,153 which was assumed, and later confirmed, 154 to function as an in situ reservoir of the highly reactive 12-electron complex [P(t-Bu) 3 )Pd(0)], that readily activates aryl halides (Scheme 19). 139 This reactivity difference between Pd[P(t-Bu) 3 ] 2 and [(P(t-Bu) 3 Pd(μ-Br))] 2 was clearly demonstrated in the C−N cross-coupling reactions as well (Figure 3).…”
Section: [L 1 Pd(i)x] 2 Dimers (X = Br I) As Precatalystsmentioning
confidence: 99%
“…150 In 2012, Gooßen's group identified it as a highly active isomerization catalyst for the synthesis of enol esters from allylic esters. 151 [(P(t-Bu) 3 Pd(μ-Br))] 2 has been employed as a precatalyst, 145,152,153 which was assumed, and later confirmed, 154 to function as an in situ reservoir of the highly reactive 12-electron complex [P(t-Bu) 3 )Pd(0)], that readily activates aryl halides (Scheme 19). 139 This reactivity difference between Pd[P(t-Bu) 3 ] 2 and [(P(t-Bu) 3 Pd(μ-Br))] 2 was clearly demonstrated in the C−N cross-coupling reactions as well (Figure 3).…”
Section: [L 1 Pd(i)x] 2 Dimers (X = Br I) As Precatalystsmentioning
confidence: 99%
“…This approach was also undertaken on a preparative scale in the case of eugenol 5 (10 mmol), with excellent results (87%). It should be noted that the palladium­(I) catalyst [Pd­(μ-Br)­(P t Bu 3 )] 2 422 was discovered by Gooβen to be a very effective isomerization catalyst for a wide variety of unsaturated systems, including that of eugenol 5 into its 1-propenyl analogue (0.05 mol % 422 , toluene, 50 °C, 2 h, 96%, E : Z = >20:1) . Of interest in terms of the mechanism is that Gooβen mentioned that the interesting palladium­(I) [Pd­(μ-Br)­(P t Bu 3 )] 2 catalyst system 422 readily transforms into a reactive palladium­(II)–hydride species, thus accounting for its reactivity.…”
Section: Transition Metal-mediated Isomerizations Of Allylbenzenesmentioning
confidence: 99%
“…PdCl 2 (MeCN) 2 has probably been the palladium catalyst of choice and is frequently used at room temperature. In terms of recent research in the area, the Lindhardt−Skrydstrup catalytic system, 511 comprised of Pd(dba) 2 , P( t Bu) 3 , and isobutyryl chloride, and the Gooβen catalyst, 525 [Pd(μ-Br)(P t Bu 3 )] 2 , appear to be excellent reagents. These complexes facilitate the isomerization of a wide range of allylbenzenes, into the desired 1-propenylbenzenes, with excellent selectivities and at low catalyst loadings (below 0.5%).…”
Section: Supported Palladium Catalystsmentioning
confidence: 99%
“…A review of the literature as well as in-house knowledge identified a range of transition metal catalysts that could potentially accomplish the isomerization reaction, and these were screened in a multiwell format in an inerted glovebox (Table 1). Conversion to the required product was observed using a number of different catalysts (entries 4, 7, 9, 10, 13, and 16), but the standout result was the use of di-μ-bromobis(tri-tert-butylphosphine)dipalladium(I) (entry 15), 20 where ca. 90% conversion was observed by HPLC analysis with ca.…”
Section: The Synthesis Of Exo-methylenementioning
confidence: 99%